Effects of choline on the phenotype of the cultured bovine preimplantation embryo - Estrada Cortés, E. (2020)
Choline is a precursor of acetylcholine, phosphatidylcholine, and the methyl-donor betaine. Reports indicate that supplementation with rumen-protected choline improves postpartum reproductive function of dairy cows. The objective was to determine whether addition of choline to culture medium of in vitro-produced embryos alters the phenotype of the resultant blastocysts. Treatments were choline chloride (ChCl; 0.004, 1.3, 1.8, and 6.37 mM) and phosphatidylcholine (1.3 mM). Treatment with 0.004 mM ChCl improved development to the blastocyst stage, increased blastocyst cell number, and increased the percentage of blastocysts that were hatching or hatched. Development was not affected by higher concentrations of ChCl but was reduced by 1.3 mM phosphatidylcholine. Treatment of embryos with 1.3 mM ChCl (but not other concentrations) increased expression in blastocysts of 11 of 165 genes examined (AMOT, NANOG, HDAC8, HNF4A, STAT1, MBNL3, SOX2, STAT3, KDM2B, SAV1, and GPAM) and decreased expression of one gene (ASS1). Treatment with 1.3 mM ChCl decreased global DNA methylation at d 3.5 of development and increased DNA methylation at d 7.5 in blastocysts. Treatment with 1.8 mM ChCl also increased methylation in blastocysts. In conclusion, addition of choline to the culture medium alters the phenotype of preimplantation bovine embryos produced in vitro. Choline chloride can act in a concentrationdependent manner to alter development, expression of specific genes, and DNA methylation.